The Effect Of Service Quality And Customer Experience On Satisfaction And Their Impact On Customer Loyalty (Survey customers of Shafira Tour & Travel Tasikmalaya) - Miftah Syamsul Arifin; Depy Muhamad Pauzy; Cece Rakhmat (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect of service quality and customer experience on satisfaction and their impact on customer loyalty at Shafira Tour & Travel Tasikmalaya. The method used in this study is a survey method with a causal research design. The population in this study is the number of orders in the last period as many as 4.784 and after being processed using the Slovin formula, the sample is taken as many as 100 respondents. The analytical tool used is path analysis. The results showed that service quality had a significant effect on satisfaction in Shafira Tour & Travel Tasikmalaya. Customer experience have a significant effect on satisfaction in Shafira Tour & Travel Tasikmalaya. Satisfaction has not been proven to be able to mediate service quality on customer loyalty through the satisfaction of Shafira Tour & Travel Tasikmalaya. Customer experience have a significant effect on customer loyalty through satisfaction in Shafira Tour & Travel Tasikmalaya.